Ultimate strength of steel–concrete–steel sandwich panels under lateral pressure loading. (15th May 2016) - Wang, Yonghui; Liew, J.Y. Richard; Lee, Siew Chin
Highlights: Steel–concrete–steel (SCS) sandwich composite panels under lateral pressure load were experimentally studied. Inflated airbag was used to apply the lateral pressure load. Bending and transverse shear resistances of SCS panels were calculated. Finite element simulation on the SCS panels was conducted. Abstract: The response behavior of steel–concrete–steel (SCS) sandwich panels without shear connectors was experimentally studied under lateral pressure loading in this paper. The loading was applied by a hydraulic actuator on an inflated airbag to assert lateral pressure on the SCS panels. The failure modes and maximum resistance of the SCS panels were obtained from the test and compared with the numerical analysis results. It was found from the experimental and numerical studies that the end plates could function as shear connectors to achieve the composite action between face plates and concrete core. Based on the experimental and numerical observations, the formulae to predict the bending resistance and transverse shear resistance of SCS panel without shear connectors were developed and the accuracy of the proposed formulae was verified by comparing with the experimental and numerical results.